Optimization and prediction of the electron–nuclear dipolar and scalar interaction in 1H and 13C liquid state dynamic nuclear polarization. Issue 11 (13th August 2015) - Wang, X.; Isley III, W. C.; Salido, S. I.; Sun, Z.; Song, L.; Tsai, K. H.; Cramer, C. J.; Dorn, H. C.
Abstract : Solution-state dynamic nuclear polarization (DNP) is a powerful tool for hyperpolarization and the study of intermolecular interactions in solution. Abstract : During the last 10–15 years, dynamic nuclear polarization (DNP) has evolved as a powerful tool for hyperpolarization of NMR and MRI nuclides. However, it is not as well appreciated that solution-state dynamic nuclear polarization is a powerful approach to study intermolecular interactions in solution. For solutions and fluids, the 1 H nuclide is usually dominated by an Overhauser dipolar enhancement and can be significantly increased by decreasing the correlation time ( τ c ) of the substrate/nitroxide interaction by utilizing supercritical fluids (SF CO2 ). For molecules containing the ubiquitous 13 C nuclide, the Overhauser enhancement is usually a profile of both scalar and dipolar interactions. For carbon atoms without an attached hydrogen, a dipolar enhancement usually dominates as we illustrate for sp 2 hybridized carbons in the fullerenes, C60 and C70 . However, the scalar interaction is dependent on a Fermi contact interaction which does not have the magnetic field dependence inherent in the dipolar interaction. For a comprehensive range of molecular systems we show that molecules that exhibit weakly acidic complexation interaction(s) with nitroxides provide corresponding large scalar enhancements. For the first time, we report that sp hybridized (H–C) alkyne systems, for example, the phenylacetylene–nitroxide system exhibit very large scalar dominated enhancements. Finally, we demonstrate for a wide range of molecular systems that the Fermi contact interaction can be computationally predicted via electron–nuclear hyperfine coupling and correlated with experimental 13 C DNP enhancements.